2003
DOI: 10.1007/s00442-003-1197-4
|View full text |Cite
|
Sign up to set email alerts
|

Feedback dynamics of grazing lawns: coupling vegetation change with animal growth

Abstract: We studied the effects of grazing by Black Brant (Branta bernicla nigricans) geese (hereafter Brant) on plant community zonation and gosling growth between 1987 and 2000 at a nesting colony in southwestern Alaska. The preferred forage of Brant, Carex subspathacea, is only found as a grazing lawn. An alternate forage species, C. ramenskii, exists primarily as meadow but also forms grazing lawns when heavily grazed. We mowed plots of ungrazed C. ramenskii meadows to create swards that Brant could select and main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
159
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(169 citation statements)
references
References 48 publications
7
159
3
Order By: Relevance
“…Madsen and C. Jaspers, unpubl.). The structuring role of goose grazing has also been demonstrated in studies employing long-term exclosures in grazed marshes (Person et al 2003;Gauthier et al 2004). Owing to its small and low leaves protruding from the moss carpet, C. subspathacea is possibly the most grazing tolerant species amongst the Carex species which may explain its dominance in the grazed part of the marsh.…”
Section: Discussionmentioning
confidence: 90%
“…Madsen and C. Jaspers, unpubl.). The structuring role of goose grazing has also been demonstrated in studies employing long-term exclosures in grazed marshes (Person et al 2003;Gauthier et al 2004). Owing to its small and low leaves protruding from the moss carpet, C. subspathacea is possibly the most grazing tolerant species amongst the Carex species which may explain its dominance in the grazed part of the marsh.…”
Section: Discussionmentioning
confidence: 90%
“…Person et al (2003) found that the areal extent of grazing lawns increased with an increase in population size in breeding areas of black brant (Branta bernicla nigricans) in southwestern Alaska. This led to improved foraging conditions which resulted in higher growth rates of goslings.…”
Section: Introductionmentioning
confidence: 99%
“…These increasing numbers have resulted in increased grazing pressure in many traditional breeding areas. Studies from these (sub-) arctic-breeding areas showed contrasting effects of increased grazing pressure on the vegetation, leading either to improved (Cargill and Jefferies 1984;Hik and Jefferies 1990;Person et al 2003) or deteriorated foraging conditions (Zellmer et al 1993;Gadallah and Jefferies 1995b;Jefferies and Rockwell 2002) with potential feedbacks on population growth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations